The New Zealand Model of Free Association: What does it Mean for New Zealand - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 2008)
Using Professor Angelo’s work in Tokelau as a starting point, Alison Quentin-Baxter examines the model of "free association" relationship that New Zealand has with the Cook Islands and with Niue, and was also to be the basis of Tokelauan self-government. She looks at both the legal and practical obligations that such relationships place on both parties, but particularly on New Zealand. The form of the model means the basis for New Zealand’s obligations to an associated state are quite different from its provision of aid to other states.